O36: DEVELOPING A TRAUMA REGISTRY IN A MIDDLE INCOME COUNTRY – BOTSWANA. (27th April 2021) - Joseph Motsumi, Mpapho; Mashalla, Yohana; Sebego, Miriam; Ho-Foster, Ari; Motshome, Paul; Mokokwe, Lebogang; Mmalane, Mompati; Montshiwa, Thapelo
Abstract: Background: Botswana has a large burden of disease from injury, but no trauma registry. This study sought to design and pilot test a trauma registry at two hospitals. Methods: A cross sectional study was piloted at a tertiary hospital and a secondary level hospital in Botswana. The study consisted of two stages: stage 1 mainly involved stakeholder consultations on existing data collection tools. Stage 2 consisted of two phases: Phase I involved retrospective collection of existing data from existing data collection tools and Phase II collected data prospectively using the proposed trauma registry prototype. Results: The pre-hospital road traffic accident data is collected using hard copy forms and some of this data is transferred to a stand-alone electronic registry. The hospital phase of road traffic accident data all goes into hard copy files then stored in institutional registry departments. The post-hospital data is also partially stored as hard copies and some data is stored in a stand-alone electronic registry. The demographics, pre-hospital, triage, diagnosis, management and disposition had a high percent variable completion rate with no significant difference between phases I and II. However, the primary survey variables in Phase I had a low percent variable completion rate which was significantly different from the high completion rates in phase II at both hospitals. A similar picture was observed for the secondary survey at both hospitals. Conclusion: Electronic trauma registries are feasible and data completion rate is high when using the electronic data registry as opposed to data collected using the existing paper-based data collection tools. Keywords: Trauma registry, Injury registry, Road Traffic Accident Trauma Registry, Road Traffic Crushes Registry, Road Accident Registry. SYSTEMATIC REVIEWS